IMPLEMENTATION OF ONLINE LEARNING FOR MEDAN CITY HIGH SCHOOL STUDENTS DURING THE PANDEMIC - Muhammad Sadri; Delyana R Pulungan (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
Although the COVID-19 pandemic has not yet fully recovered, the online learning process must still be carried out as an effort to educate the lives of the nation's generation. The purpose of this study was to examine in more depth the online learning strategies carried out by schools. This research was conducted in the first week to the fourth week of February 2022. The data collection techniques were in the form of observation, interviews, and documentation studies. The researcher serves as the main tool for data collection. The main data collection techniques are through interviews, explanations and documentation. The results showed that there were various online learning strategies carried out by the school, including icebreakers and openers, student expeditions, PCT (Purposive Creative Thinking), P2P (Peer to Peer interaction), streaming experts, and mental gymnastics. This learning strategy is carried out with the hope that it can foster meaningful learning in learning